ONE HUNDRED YEARS SINCE THE DRAFT OF THE STATUTE OF HOLY MOUNTAIN: LEGAL REGULATION UP TO THE 10TH CENTURY AND ITS INFLUENCE ON THE CURRENT CONSTITUTIONAL CHARTER - Vasiljević, Aleksandar (Zbornik radova Pravnog fakulteta u Novom Sadu, 2024)
The Constitutive Charter of Mount Athos (1926) is a legal source whose Draft from 1924 marks its centennial anniversary. In the research, the author applies a comparativist approach to the legal arrangement of Mount Athos until the 10th century and its effect on the current Statute. The forms of Holy Mountain’s arrangement, based on the Chair of the elders, Athanasius and Tsimiski’s typic, managed to survive in fragments despite military occupations, political and other repercussions. The regulation of legal subjectivity over the Athos peninsula is a crucial circumstance and the most important contribution to the stability and durability of the relevant source of law. The author introduces us to the wide range of constitutional and legal solutions offered by the Constitutional Charter, as well as to the Decree by which the Greek state officially confirmed and presented this important legal act of Mount Athos. The author’s goal is to use research to encourage the professional public to celebrate the double jubilee in 2026: one hundred years since the adoption and one hundred years of application of the Constitutive Charter.